PERAN STRATEGIS BISNIS DIGITAL DALAM PROMOSI DAN PENGEMBANGAN PARIWISATA KYOKKO BEACH LAMPUNG - Budiman, Valdi Mughni (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This research explores the strategic significance of digital business in enhancing the promotion and growth of the Kyokko Beach tourist destination in Lampung. As a developing tourism site, Kyokko Beach encounters obstacles related to market reach and public exposure, mainly due to the lack of traditional promotional efforts and limited integration of digital technologies. Employing a descriptive qualitative methodology, data were gathered through field observations, interviews with local tourism actors, and a review of pertinent literature. The results demonstrate that leveraging digital business tools—such as social media engagement, online booking systems, and the digital marketing involvement of local MSMEs—has notably boosted tourist numbers and reinforced the destination’s online presence. Additionally, the study highlights persistent issues like inadequate digital skills and insufficient technological infrastructure. Unlike prior research that predominantly examined well-established tourist spots, this study contributes novel perspectives by focusing on an emerging destination through a community-driven approach. The proposed framework for digitalization underscores the value of multi-stakeholder cooperation, community empowerment, and the implementation of sustainable and adaptive digital management practices.